Patient mistreatment, social sharing of negative events and emotional exhaustion among Chinese nurses: the combined moderating effect of organizational support and trait resilience - Wei Yan; Xiu Chen; Di Xiao; Huan Wang; Xin Du; Li Li; Chunjuan Xu; Caiping Song (BMC, 2024)
Abstract Background As a primary form of work-related violence in the healthcare sector, patient mistreatment negatively impacts nurses' well-being. To date, there has yet reached a definitive conclusion on the mediating mechanism and boundary conditions behind the influence of patient mistreatment on nurses' emotional exhaustion. Methods This study employed a convenience sampling method to recruit a sample of 1672 nurses from public hospitals in Western China. The data were collected through anonymous self-report questionnaires and analyzed using hierarchical regression and conditional processes to investigate a theoretical framework encompassing patient mistreatment, emotional exhaustion, social sharing of negative events, organizational support, and trait resilience. Results Patient mistreatment led to emotional exhaustion among nurses (β = 0.625, p <.001), and social sharing of negative events mediated this positive relationship (effect = 0.073, SE = 0.013). The combined effects of organizational support and resilience moderated the mediating effect of the social sharing of negative events between patient mistreatment and emotional exhaustion (β=-0.051, p <.05). Specifically, nurses with a high level of resilience would benefit from organizational support to alleviate emotional exhaustion caused by patient mistreatment. Conclusions This study validated a significant positive association between patient mistreatment and emotional exhaustion, which aligns with previous research findings. Integrating conservation of resources theory and goal progress theory, we addressed previous contradictory findings on the impact of social sharing of negative events on emotional exhaustion. Social sharing of negative events served as a mediator between patient mistreatment and emotional exhaustion. Additionally, the moderating effect of organizational support on the relationship between social sharing of negative events and emotional exhaustion depended on individual trait of resilience.